ANALISIS FLYPAPER EFFECT BERDASARKAN PEMETAAN INDEKS KEMAMPUAN KEUANGAN DAN PERTUMBUHAN EKONOMI PADA KABUPATEN DAN KOTA DI PROVINSI KALIMANTAN BARAT - B01111006, Tria Monawaroh (Jurnal Pembangunan dan Pemerataan, 2015)
Abstract The aim of this research was to reveal the phenomenon of the flypaper effect that occurred in districts and cities in West Kalimantan based on the financial capability index and economic growth. Share value and growth were used in mapping the districts and cities through quadrant analysis, with Public Allocation Funds, Revenue Sharing Funds and Locally Generated Revenues as the independent variables and Regional Expenditures as the dependent variable used through panel data regression analysis. The empirical results of this research showed that the phenomenon of the flypaper effect occurred in districts and cities that located outside the ideal quadrant even though the Financial Capability index was above average. Meanwhile, the General Allocation Funds, Revenue Sharing Funds, and Locally Generated Revenues also proved to have significant and positive influence on the Regional Expenditures. Keywords: flypaper effect, General Allocation Fund, Revenue Sharing Fund, Locally Generated Revenue, Regional Expenditure, Financial Capability Index